A one-dimensional organic-inorganic hybrid copper(I)-halide with broadband emission. (April 2023) - Ma, D.; Lan, Y.; Zhang, D.; Qin, X.; Yang, Z.; He, H.; Dai, X.; Ye, Z.; Cao, X.
Abstract: Organic-inorganic perovskite materials have shown excellent performance and strong competitiveness in high-performance photovoltaic and optoelectronic devices. Besides the color-tunable and narrow-band emissions realized in hybrid perovskites, broadband emission from lead-halide perovskites has also attracted strong interest for applications in the next generation of solid-state lighting. Although great progress has been made in lead halide perovskites, a very important aspect that hinders their commercial exploitation is the severe lead toxicity. In this research, a lead-free copper(I)-iodine hybrid was synthesized by a solution evaporation method at room temperature. Single crystal X-ray diffraction shows that this hybrid possesses the chemical formula of C6 H5 CH2 CH2 NH3 CuI2 . The C6 H5 CH2 CH2 NH3 CuI2 belongs to the monoclinic phase with the C2/c space group, where the edge-sharing [CuI4 ] tetrahedral chains are separated by organic C6 H5 CH2 CH2 NH3 + ions, exhibiting one-dimensional (1D) crystal structure. The optical band-gap of C6 H5 CH2 CH2 NH3 CuI2 was determined to be 4.02 eV. The photoluminescence (PL) spectrum shows a broadband emission ranging from 380 nm to 780 nm and peaks at 542 nm together with a small peak at 336 nm, which can be attributed to the emission of self-trapped exciton (STE) and free exciton (FE), respectively. The large Stokes shift of 230 nm between the PL and photoluminescence excitation (PLE) as well as the broad emission was ascribed to the Jahn–Teller lattice distortion of [CuI4 ] tetrahedra. The reduced 1D characteristic facilitates the tetrahedral distortion. PL decay analysis shows that the average lifetime of STE is about 66.9 ns? Temperature and time-dependent PL measurements show that the normal working temperature of this luminescent material should be no higher than 100 °C. Theoretical calculations were performed to better understand this compound. The successful synthesis and preliminary optical investigations on C6 H5 CH2 CH2 NH3 CuI2 can be of great significance for offering more environmental-benign options in both solid-state lighting and other perovskite optoelectronic devices. Graphical abstract: A 1D lead-free copper(I)-iodine hybrid of C6 H5 CH2 CH2 NH3 CuI2 with broadband emission was synthesized. Image 1 Highlights: A lead-free one-dimensional copper(I)-iodine hybrid compound. Broadband emission ranging from 380 nm to 780 nm. Average lifetime for the self-trapped exciton of about 66.9 ns?